Penggunaan Alat Bantu pada Kelompok Nelayan Penangkap Ikan Pelagis Campuran di Kabupaten Barru - Andi Adam Malik; Nurhapsa Nurhapsa; Muhammad Kusnady Tabsir (DEDIKASI, 2018)
The purposes of this service are to 1) increase catch and reduce operational costs through the supportingtechnology of fishing equipment, 2) improve the ability of Mixed Pelagic fishermen to use fishing aids such as GPS,Fish finder, use of shallow marine FADs and to read fishing maps independently, 3) train and practice the use of iceto preserve the caught fishes in accordance with the provisions, and 4) train and practice sweet pindang and fishpreservation. The benefits of this program are to increase the catch and reduce the operational costs of mixed pelagicfishermen. The method used in implementing science and technology for the community is Participatory RuralAppraisal (PRA). The implementation of this activity through counseling, training and demonstration and evaluationto see the effectiveness of the program so that the program will be socialized efficiently. The implementation offishing tools (GPS, fish finder, shallow marine FADs), read fishing maps independently, and the use of ice topreserve fish caught in accordance with the provisions, fish processing such as making sweet pindang andpreserving fish and potential maps fish catching).